RATE OF POSITIVE BLOOD CULTURES AND ANTIMICROBIAL RESISTANCE CHARACTERISTICS OF BACTERIA ISOLATED FROM BLOOD CULTURE SAMPLES IN CHILDREN AT TRA VINH OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Introduction: Sepsis is a severe and rapidly progressive infectious condition with a high mortality rate, particularly in neonates and young children. Bacteria are the primary causative agents of sepsis, and the increasing prevalence of antimicrobial resistance has posed significant challenges to treatment. Blood culture remains the gold standard for identifying causative pathogens and determining antimicrobial susceptibility. Objectives: To determine the rate of positive blood cultures and to assess the antimicrobial resistance patterns of selected bacterial isolates from positive blood cultures in pediatric patients at Tra Vinh Obstetrics and Pediatrics Hospital.Subjects and Methods: Blood culture results of pediatric patients at Tra Vinh Obstetrics and Pediatrics Hospital were analyzed in a descriptive cross-sectional study conducted from May 5, 2025 to July 13, 2025.Results: The rate of positive blood cultures was 19.75%. Gram-positive bacteria were predominant, including Staphylococcus epidermidis, Staphylococcus haemolyticus, and Staphylococcus aureus. Gram-negative bacteria mainly included Escherichia coli and Enterobacter cloacae. Gram-positive isolates showed high resistance to beta-lactams, erythromycin, and clindamycin, but remained susceptible to vancomycin and linezolid.Conclusion: Among 81 blood culture samples, 16 were positive, accounting for 19.75%. The study observed a difference in the rate of positive blood cultures between pediatric patients with and without fever.
Keywords: sepsis, blood culture, children, antimicrobial resistance.